2017
DOI: 10.1039/c6pp00334f
|View full text |Cite
|
Sign up to set email alerts
|

Parietin: an efficient photo-screening pigment in vivo with good photosensitizing and photodynamic antibacterial effects in vitro

Abstract: The photophysical, photoinduced pro-oxidant and antibacterial properties in vitro of the natural occurring parietin (PTN; 1,8-dihydroxy-3-methoxy-6-methyl-9,10-anthraquinone) were evaluated. PTN was extracted from the lichen identified as Teloschistes flavicans (Sw.) Norm. (Telochistaceae). Results indicate that in chloroform solution, PTN presents spectroscopic features corresponding to an excited-state intramolecular proton-transfer (ESIPT) state with partial keto-enol tautomerization. In argon-saturated sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…One of the main advantages of PDT is the possibility to combine this treatment with other complementary techniques [1]. For instance, combinations with photothermal therapy (PTT), chemotherapy, or immunotherapy have been reported [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main advantages of PDT is the possibility to combine this treatment with other complementary techniques [1]. For instance, combinations with photothermal therapy (PTT), chemotherapy, or immunotherapy have been reported [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These optically silent PS prodrugs are photodynamically inactive until they encounter the proper chemical or biological trigger, inducing a conformation change and becoming photodynamically active. Such chemical or physiological triggers include (1) pH, (2) redox potential, (3) enzymatic activities, (4) DNA, or (5) temperature. This review is dedicated to the development and testing of such photosensitizer prodrugs.…”
Section: Introductionmentioning
confidence: 99%
“…Bleaching reactions are promoted in proton-donating solvents. Recent studies have shown that a number of deactivation pathways can occur in anthraquinones, including emission from tautomeric states following excited state internal electron transfer and from population of a dark, non-radiative state that irreversibly leads to a colorless molecule [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…•- [20,21]. In another study, the antibiofilm activity of parietin has been demonstrated against S. aureus and E. faecalis [22], which is particularly interesting as biofilms are implicated in 80 % of human microbial infections.…”
Section: Quinone Derivativesmentioning
confidence: 99%